Effectiveness of three-dimensional printed and virtual reality models in learning the morphology of craniovertebral junction deformities: a multicentre, randomised controlled study - Ye Tian; Xi Zhou; Yu He; Siyi Cai; Haomin Cui; Dongsheng Zhou; Fu Wang (BMJ Open)
Objectives To compare the effectiveness of three-dimensional printed (3DP), virtual reality (VR) and conventional normal physical (NP) models in clinical education regarding the morphology of craniovertebral junction (CVJ) deformities.Design Prospective, multicentre, randomised controlled study.Setting Three teaching hospitals in China.Participants Onehundred and fifty-three participants in their first year of a 3-year medical residency programme.Interventions All participants were randomised to one of the three groups to learn the morphology of CVJ deformities using 3DP, VR or NP models.Primary outcome measures The objective outcomes were evaluated using three-level objective testing. In the first-level test, the participants were required to identify 15 anatomical landmarks on radiographs without CVJ deformities. In the second-level test, all participants were asked to identify the same 15 landmarks on radiographs showing classic CVJ deformities. In the third-level test, the participants were required to describe the key features of three classic cases of CVJ deformities depicted on radiographs. Each participant was also asked to answer four subjective questions to evaluate the importance and usefulness of the educational materials.Results In the first-level test, the 3DP, VR and NP groups achieved similar correct rates. In the second-level test, the correct rate was higher in the 3DP group (82.1%±13.6%) than the VR and NP groups (76.9%±16.9% and 69.9%±20.0%, p=0.002). In the third-level test, the 3DP group achieved better correct rates regarding the description of key CVJ deformities features (66.2%±20.0%, p=0.049) than the other groups. The subjective tests showed that the 3DP model method was considered the most valuable approach for learning CVJ deformities.Conclusions The objective and subjective results show that the 3DP model is more effective teaching instrument than the NP model for learning the pathomorphology of CVJ deformities. The VR model also showed great efficacy, second to 3DP model, in improving participants’ understanding of CVJ deformities.